Care of the Laparoscopic Nissen Fundoplication Patient - Aronson, B.S.; Yeakel, S.; Ferrer, M.; Caffrey, E.; Quaggin, C. (Gastroenterology Nursing, 2001)
Gastroesophageal reflux disease can usually be successfully managed with conservative medical treatment. Anti-reflux surgery is a safe alternative when treatment fails or patients desire a more definitive treatment option. Through a case study approach, this article describes the indications for surgery, the essentials of the authors’ multi-disciplinary approach to care and the components of a well-designed education plan for a patient undergoing laparoscopic Nissen fundoplication. Although most patients do well after surgery, diligent nursing care is required before and after surgery to prevent or manage complications and ensure patients have a rapid recovery and successful outcome. © 2001 Lippincott Williams & Wilkins, Inc.
3 citations (Crossref) [2023-10-31]
Keywords: Fundoplication; Gastroesophageal Reflux; Gastroscopy; Humans; Male; Middle Aged; Patient Care Team; Patient Discharge; Patient Education; Patient Selection; Perioperative Care; Treatment Outcome; case report; dept.nur; gastroesophageal reflux; gastroscopy; hospital discharge; human; male; methodology; middle aged; nursing; organization and management; patient care; patient education; patient selection; perioperative period; review; stomach fundoplication; treatment outcome

Pain in older adults - Wallace, M. (Annals of Long-Term Care, 2001)
Pain is a prevailing clinical problem among older adults resulting in systemic agitation and altered quality of life. Although the possibility remains that older adults experience and report less pain, the need exists to objectively evaluate pain in order to provide the most effective pain management. Several standardized tools are available to assess pain in older adults at baseline and at subsequent, frequent intervals. Following an objective assessment, pain may be managed with pharmacologic and nonpharmacologic methods.
Keywords: Alzheimer disease; acetylsalicylic acid; aged; amitriptyline; analgesic agent; anticonvulsive agent; carbamazepine; choline magnesium trisalicylate; clonazepam; codeine; corticosteroid; dementia; dept.nur; desipramine; dose response; doxepin; drug effect; drug formulation; drug indication; fentanyl; gabapentin; human; hydrocodone; hydromorphone; ibuprofen; imipramine; intravenous anesthetic agent; local anesthetic agent; morphine sulfate; naproxen; narcotic analgesic agent; nonsteroid antiinflammatory agent; nortriptyline; opiate; oxycodone; pain; pain assessment; paracetamol; prednisone; review; side effect; tricyclic antidepressant agent; unindexed drug; visual analog scale; ⛔ No DOI found